ANALYSIS OF WORK QUALITY AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AT THE MEDAN SUNGGAL DISTRICT OFFICE - Siti Arnisah; Mesra B; Elfitra Desy Surya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the effect of work quality and work environment on employee performance, both directly and indirectly through job satisfaction as an intervening variable at the Medan Sunggal District Office. This study uses a quantitative approach with a survey method. The population in this study were all State Civil Apparatus (ASN) at the Medan Sunggal District Office, totaling 90 people. The data analysis technique used was Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of the SmartPLS 3.0 application. The results of the study indicate that work quality has a positive and significant effect on employee performance both directly and through job satisfaction. The work environment also has a positive but insignificant effect on employee performance, but through job satisfaction it has a positive and significant effect. In addition, job satisfaction has been shown to have a positive and significant effect on employee performance. Job satisfaction also significantly mediates the effect of work quality and work environment on employee performance. These findings indicate that improving work quality and a good work environment will encourage higher job satisfaction, which ultimately improves employee performance.